Plutarco - Epítome da Comparação de Aristófanes e Menandro - Ana Maria César Pompeu (Classica Digitalia: Autores Gregos e Latinos: textos, 2017)
This volume offers a Portuguese translation of the Epitome of the comparison between Aristophanes and Menander, by Plutarch. Beside some footnotes, there is an introduction including reflections about the three authors involved: the two comediographers and Plutarch himself in his analysis of comic poetry. In general, this text represents an exercise of critical reception, from Antiquity, of Greek comedy main authors, in its two specific moments, Archaia and Nea.